2020
DOI: 10.1002/dc.24538
|View full text |Cite
|
Sign up to set email alerts
|

The apparition macrophage and Döderlein bacillus is negatively correlated in class I Papanicolaou smear: A morphological examination

Abstract: Background: Nonspecific vaginitis, also known as Bacterial vaginosis, unlike genital candidiasis and trichomoniasis, is caused by microbiome breakdown. Döderlein's bacillus are gram-positive bacillus that form a microbiome, reproduce in the female vagina after gaining sexual maturity, secrete lactic acid, and prevent the growth of other vaginitis-causing bacteria. Clue cell are squamous epithelial cells with Gardnerella sp. attached to their cell surface. The presence of clue cell is one of the diagnostic crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The results indicated that combination of Nifuratel tablet and Baofukang suppository enhanced the disappearance of clinical manifestations, reduced recurrence and the expression levels of inflammatory factors, and significantly improved the safety of treatment. In a previous study [20], it was demonstrated a group of vaginitis patients given combined treatment with Nifuratel tablets and Baofukang suppository significantly performed better than those on monotherapy, with respect to treatment effectiveness, time taken for disappearance of clinical manifestations, and recurrence after treatment. In addition, there was no significant difference between the two monotherapy groups in overall treatment effectiveness, time taken for disappearance of clinical manifestations, and recurrence, indicating that combination of Nifuratel tablets with Baofukang suppository produced a desirable effect and high safety in the treatment of pregnant women with vaginitis.…”
Section: Discussionmentioning
confidence: 94%
“…The results indicated that combination of Nifuratel tablet and Baofukang suppository enhanced the disappearance of clinical manifestations, reduced recurrence and the expression levels of inflammatory factors, and significantly improved the safety of treatment. In a previous study [20], it was demonstrated a group of vaginitis patients given combined treatment with Nifuratel tablets and Baofukang suppository significantly performed better than those on monotherapy, with respect to treatment effectiveness, time taken for disappearance of clinical manifestations, and recurrence after treatment. In addition, there was no significant difference between the two monotherapy groups in overall treatment effectiveness, time taken for disappearance of clinical manifestations, and recurrence, indicating that combination of Nifuratel tablets with Baofukang suppository produced a desirable effect and high safety in the treatment of pregnant women with vaginitis.…”
Section: Discussionmentioning
confidence: 94%